2016
DOI: 10.1007/s40121-016-0138-6
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Omics Technologies in Lyme Disease Biomarker Discovery and Early Detection

Abstract: Lyme borreliosis (LB) is the most prevalent arthropod-borne infectious disease in North America and many countries of the temperate Northern Hemisphere. It is associated with local and systemic manifestations and has persistent post-treatment health complications in some individuals. Innate and acquired immunity-related inflammation is likely to play a critical role in both host defense against Borrelia burgdorferi and disease severity. Large-scale analytical approaches to quantify gene expression (transcripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 89 publications
(170 reference statements)
0
14
0
4
Order By: Relevance
“…In addition, the AT genotype at rs4073 in IL8 [16] and the AG at rs909253 in LTα, also known as TNF-β [16,26], were associated with the inflammatory response [13]. In the present study, the genotypes identified to play a role in IAV, were also rep- compared to those with "no-risk" genotype.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In addition, the AT genotype at rs4073 in IL8 [16] and the AG at rs909253 in LTα, also known as TNF-β [16,26], were associated with the inflammatory response [13]. In the present study, the genotypes identified to play a role in IAV, were also rep- compared to those with "no-risk" genotype.…”
Section: Discussionmentioning
confidence: 58%
“…Such polymorphisms in hypercytokinemia genes are associated with an increased potential to synthesize cytokines and chemokines and influence the nature and effectivness of the inflammatory immune response [13,27]. Overall, risk alleles of IL8 and TNF-β were associated with a 1.5 to 3-fold increased risk of IAV infection and with a 1.2 to 2.4 increased risk of death [16,28]. This observation may facilitate the characterization of genetic factors and downstream protein biomarkers that can be employed in identifying individuals at high risk of disease severity upon and during infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infected tissues typically display a mononuclear-type inflammation, with predominating macrophages, dendritic cells, and plasma cells [12, 16]. However, the underlying mechanisms of this inflammatory response and resolution are not clear [13, 14]. The initial innate immune response begins with a signaling cascade which is promoted by cytokines, eicosanoids and related lipid mediators [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of cytokines in the mediation of the inflammatory process in LB has been well described [13], no study has systematically evaluated the role of PGs and related lipid mediators in the induction and resolution of inflammation in LB. Given the high level of inflammation-related long-term effects of LB as well as the widespread use of COX-specific inhibitors and non-steroidal anti-inflammatory drugs (NSAIDs) in the treatment of LB [21], it is critical to understand the role of bioactive lipid mediators in LB to provide better approach for symptoms resolution and LB treatment.…”
Section: Introductionmentioning
confidence: 99%